Age- and sex-specific characteristics of right ventricular compacted and trabeculated myocardium by cardiac magnetic resonance. (4th February 2022) - Szucs, A; Kiss, AR; Gregor, ZS; Furak, A; Szabo, LE; Dohy, ZS; Grebur, K; Merkely, B; Vago, H
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Ministry for Innovation and Technology in Hungary within the framework of the Therapeutic Development and Bioimaging Programs of Semmelweis University. National Research, Development and Innovation Fund of Hungary, financed under the NVKP_16 funding scheme. The sex-specific characteristics of right ventricular compacted (RV-CM) and RV-trabeculated myocardial mass (RV-TM) over time and the determinants of RV myocardium are less well studied; however, in different conditions,  these might provide additional information to the diagnosis. We aimed to describe the age- and sex-specific characteristics of RV-CMi, RV-TMi, and RV volumetric and functional parameters and investigate the determinants of RV myocardial mass with CMR. Two hundred healthy Caucasian volunteers free of known cardiovascular or systemic diseases were enrolled in this study. Four different age groups were established with equal numbers of males and females: Group A (n = 50, 20-29 years, mean age: 24.3 ± 3.2 years), Group B (n = 50, 30-39 years, mean age: 33.6 ± 2.6 years), Group C (n = 50, 40-49 years, mean age: 44.7 ± 2.7 years),  and Group D (n = 50, ≥ 50 years, mean age: 55.1 ± 3.9 years). RV volumetric and functional,  RV-CMi and RV-TMi values were measured with a threshold-based postprocessing method for CMR. The volumetric parameters,  RV-CMi,  and RV-TMi were larger in males,  and the ejection fraction (EF) was higher in females. The RV-CMi did not correlate with age in either of the sexes,  while the RV-TMi decreased with age in females but remained stable in males. The RV-TMi and RV-CMi correlated positively with RV volumetric parameters, the left ventricular (LV)-CMi, the LV-TMi, and each other in both sexes. LV-TMi, LV-CMi, RV end-systolic volume, and sex were independent predictors of RV-TMi. Understanding the natural history of RV-trabeculated and RV-compacted myocardium might have additive value in diagnosing different conditions with RV hypertrophy or hypertrabeculation.